1984
DOI: 10.2307/3899628
|View full text |Cite
|
Sign up to set email alerts
|

Ozone-Treated Mesquite for Supplementing Steers in West Texas

Abstract: Ozonated-mesquite was compared with cottonseed hulls as the fiber base in supplemental rations fed to growing steers under range conditions. Average daily gains of steers fed the 2 rations for the 2 winter feeding periods were similar. Similarities in concentrations of acetic, propionic, and butyric acids, and acetic:propionic acid ratios between rations indicated no alterations in production of these acids as affected by composition or physical form of the ozonated-mesquite. Therefore, ozonated-mesquite appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Ozonolysis improved the digestibility of wheat straw (Triticum aestiuum L.) (Ben-Ghedalia and Miron, 1981), cotton straw (Gossypium hirsutum L.) , grape branches (Ben-Ghedalia, 1982), and mesquite (Proseopisis sp.) (Bryant et al, 1984). have shown that ozone treatment makes cell wall polysaccharides more available for digestion by rumen microorganisms when compared to untreated or sodium hydroxide treated straw in feeding trials using cannulated sheep.…”
mentioning
confidence: 99%
“…Ozonolysis improved the digestibility of wheat straw (Triticum aestiuum L.) (Ben-Ghedalia and Miron, 1981), cotton straw (Gossypium hirsutum L.) , grape branches (Ben-Ghedalia, 1982), and mesquite (Proseopisis sp.) (Bryant et al, 1984). have shown that ozone treatment makes cell wall polysaccharides more available for digestion by rumen microorganisms when compared to untreated or sodium hydroxide treated straw in feeding trials using cannulated sheep.…”
mentioning
confidence: 99%